2001
DOI: 10.1046/j.1365-2958.2001.02482.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of the response regulator RssB in σS recognition and initiation of σS proteolysis in Escherichia coli

Abstract: SummaryIn growing Escherichia coli cells, the master regulator of the general stress response, s S (RpoS), is subject to rapid proteolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
78
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(82 citation statements)
references
References 47 publications
3
78
1
Order By: Relevance
“…It nevertheless displays residual activity that supports S degradation at a reduced rate ( Fig. 4D; Klauck et al 2001). In the strains used in Figure 4A and B, these rssB alleles were plasmid expressed under the control of the araBAD promoter (in a rssBϻTn10 genetic background; in the absence of inducer, basal RssB expression from these constructs produces cellular RssB levels comparable to those in wild-type strains [Klauck et al 2001]).…”
Section: The Histidine Sensor Kinase Arcb Stimulates S Proteolysis Bymentioning
confidence: 97%
See 4 more Smart Citations
“…It nevertheless displays residual activity that supports S degradation at a reduced rate ( Fig. 4D; Klauck et al 2001). In the strains used in Figure 4A and B, these rssB alleles were plasmid expressed under the control of the araBAD promoter (in a rssBϻTn10 genetic background; in the absence of inducer, basal RssB expression from these constructs produces cellular RssB levels comparable to those in wild-type strains [Klauck et al 2001]).…”
Section: The Histidine Sensor Kinase Arcb Stimulates S Proteolysis Bymentioning
confidence: 97%
“…Using the direct radioactive transphosphorylation assay as well as the functional RssB-S interaction assay, we found that this was not the case (data not shown). This indicates that ArcB-dependent phosphorylation of RssB is a one-way reaction and that RssB is dephosphorylated by other factors, perhaps as part of its proteolytic targeting cycle (Klauck et al 2001). This is in contrast to ArcA, for which ArcB can act as a phosphatase (Georgellis et al 1998).…”
Section: Arcb Phosphorylates and Thereby Activates The S Proteolysismentioning
confidence: 99%
See 3 more Smart Citations